Brush Sign Is Associated With Increased Severity in Cerebral Venous Thrombosis. Issue 6 (June 2019) - Aguiar de Sousa, Diana; Lucas Neto, Lia; Jung, Simon; Penas, Sara; Panos, Leonidas; Heldner, Mirjam R.; Fischer, Urs; Arnold, Marcel; Canhão, Patrícia; El-Koussy, Marwan; Ferro, José M.; Hakim, Arsany
Abstract : Background and Purpose—: The brush sign (BS) is an abnormally accentuated signal drop of the subependymal and deep medullary veins in paramagnetic-sensitive magnetic resonance sequences, previously described in acute ischemic stroke. We aimed to describe the BS in patients with thrombosis of the cerebral veins and sinuses and explore its association with clinical severity, thrombosis extent, parenchymal brain lesion, and clinical prognosis. Methods—: We assessed consecutive adult patients admitted to 2 university hospitals with diagnosis of acute thrombosis of the cerebral veins and sinuses and imaging assessment with magnetic resonance imaging, including paramagnetic-sensitive sequences. Demographics, imaging findings, clinical presentation, and functional outcome at 3 months were analyzed according to the presence of BS. Results—: In 118 patients included, BS was observed in gradient-echo T2*weighted (T2*WI) in 16% and susceptibility-weighted imaging in 13% of cases. All patients with BS had thrombosis of the superior sagittal sinus, straight sinus, or deep venous system. BS was associated with ipsilateral parenchymal lesion (odds ratio, 6.4; 95% CI, 1.9–21.1; P =0.002) and higher thrombus load (median [interquartile range] 5 [4–6] versus 2 [2–4]); P <0.0001). BS was also associated with focal neurological deficits (OR 4.2; 95%CI, 1.4–12.7, P =0.01). The functional outcome at 3 months was not significantly different in patients with BS. Conclusions—: BS in T2*WI and susceptibility-weighted imaging was observed in approximately one in 7 patients with acute thrombosis of the cerebral veins and sinuses. BS was significantly associated with ipsilateral parenchymal brain lesion, extent of thrombosis, and manifestation with focal neurological deficits. This suggests that BS can represent a marker of severity in thrombosis of the cerebral veins and sinuses. Abstract : Supplemental Digital Content is available in the text.